Synthesis of an acidic biomorphic carbon-based catalyst for simultaneous esterification and transesterification reactions - Herrera-Delgado, María Concepción (www.europacat2017.eu, 2017)
The activation of cellulose followed by sulfonation produces a biomorphic functionalized carbon material with acid catalytic activity as a solid-acid replacement for homogeneous catalysts. The carbon-based material contains carboxylic and sulfonic acid groups and exhibits high catalytic performance for liquid-phase acid-catalyzed reactions in presence of water. The activation of cellulose at high temperature (600ºC) followed by sulfonation also results in an amorphous carbon with an acidity value close to 1.52 mmol.g-1. The catalytic test shows that the sulfated carbon has enough amount of sulfonic acid groups and exhibit high catalytic activity and stability for esterification and tranesterification of raw materials; achieving a comversion value close to 90.5% at 2h of reaction comparable to an homogeneous catalysts. Structural and active site analyses suggest that the marked difference in catalytic activity is due to the accessibility of reactants to sulfonic acid groups in the carbon structure.
Keywords: Energía de biomasa; Acid catalyst; Biodiesel; Esterification; Transesterification